Search for heavy vector-like quarks coupling to light quarks in proton-proton collisions at root s=7 TeV with the ATLAS detector - Onofre, A. (2012)
This Letter presents a search for singly produced vector-like quarks, Q, coupling to light quarks, q . The search is sensitive to both charged current (CC) and neutral current (NC) processes, pp→Qq→Wqq′pp→Qq→Wqq′ and pp→Qq→Zqq′pp→Qq→Zqq′ with a leptonic decay of the vector gauge boson. In 1.04 fb−11.04 fb−1 of data taken in 2011 by the ATLAS experiment at a center-of-mass energy View the MathML sources=7 TeV, no evidence of such heavy vector-like quarks is observed above the expected Standard Model background. Limits on the heavy vector-like quark production cross section times branching ratio as a function of mass mQmQ are obtained. For a coupling κqQ=v/mQκqQ=v/mQ, where v is the Higgs vacuum expectation value, 95% C.L. lower limits on the mass of a vector-like quark are set at 900 GeV and 760 GeV from CC and NC processes, respectively.